Pharmacological Evaluation of Novel Indole Derivative for Analgesic Activity in Experimental Rats - Aasif, Mohd (International Journal of Pharmaceutical & Biological Archive, 2022)
Pain is an unpleasant sensory and emotional experience that is subjective. The prevalence of pain increases in both developed and developing countries. In this paper, we report the synthesis of indole derivatives (M1-M4) by reacting 2-chloro-1-(1H-indol-1-yl)ethanone which react with various substituted phenol. The structure of synthesized indole derivatives was confirmed by infrared and proton nuclear magnetic resonance spectral. The subacute toxicity and acute toxicity study demonstrated that compound M3 does not significantly alter biochemicals and histopathology change in rats. The analgesic activity was evaluated in vivo using rats’ acute pain models (Haffner’s tail clip, hot plate, and acetic acid-induced writhing tests). Treatment of compound M3 significantly increased pain threshold in a tail clip and hot plate and reduced the number of acetic acid writhing in rats. Hence, compound M3 showed good analgesic activity, which is demonstrated by Haffner’s tail clip, hot plate, and acetic acid-induced writhing tests for acute pain models. Overall, this study suggested that compound M3 is safe and promising analgesic activity.